2023
DOI: 10.3390/ani14010113
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Production Performance, Health Status, and Gut Microbiota of Meat Rabbit Reared in Semi-Confined Conditions

Dingcheng Ye,
Xiaoning Ding,
Shuo Pang
et al.

Abstract: In this study, we investigated the variations in production performance, health status, and gut microbiota of meat rabbits raised in the semi-confined barn during summer and winter. Compared to summer, rabbits reared in winter possessed significantly higher slaughter weight and carcass weight. Rabbits fed in the summer were more vulnerable to different stressors, which led to increased protein levels of HSP90, IL-1α, IL-1β, IL-2, and concentrations of MDA, but declined GSH and SOD activities. Additionally, sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…Research by D. Ye et al (2023) showed that changes in cold and warm seasons negatively affect intestinal microflora, immunity, and productivity. Researchers have proposed strategies to mitigate the effects of off-season changes, but have not provided a way to avoid this problem.…”
Section: Introductionmentioning
confidence: 99%
“…Research by D. Ye et al (2023) showed that changes in cold and warm seasons negatively affect intestinal microflora, immunity, and productivity. Researchers have proposed strategies to mitigate the effects of off-season changes, but have not provided a way to avoid this problem.…”
Section: Introductionmentioning
confidence: 99%